Regional Matching of Hydrogen Supply and Demand for Off-Road Vehicle Operations in Great Britain - Ahmed, Tariq (Cranfield University, 2025)
Off-road vehicles, including agricultural equipment, construction plant, and road rail vehicles (RRVs), account for a significant share of UK diesel use, yet have received limited attention in decarbonisation planning. In parallel, the UK is investing heavily in green hydrogen production through the Hydrogen Allocation Rounds. Understanding how off-road vehicle demand aligns with committed supply is, therefore, critical to meeting net-zero targets. This study quantifies hydrogen demand for off-road vehicles at the national and regional scales and compares it with HAR-funded green hydrogen projects. The analysis combines the Climate Change Committee’s Balanced Net Zero pathway with regional diesel baselines and HAR project-level capacity data to generate the first NUTS Level 1 forecasts of supply and demand dynamics in Great Britain till 2050. A bottom-up approach was applied to estimate RRV demand using unique operational datasets from Network Rail. Results show hydrogen demand increases from 46 kt in 2030 to 481 kt in 2050. Construction plants drive the early demand in the 2020s and 2030s, before agricultural equipment becomes the dominant consumer by 2050. While RRVs remain a minor contributor throughout. On the supply side, HAR 1 and HAR 2 projects provide only 58 kt of hydrogen production per year on average, leading to an initial national supply-demand surplus of 12 kt in 2030 but a deep deficit of 423 kt by 2050. On a regional level, the North East is the only region with a supply-demand surplus in 2050, while the South East and East of England face significant shortfalls. The findings confirm hydrogen’s central role in decarbonising off-road vehicles and highlight the urgency of aligning new HAR project capacity with high-demand regions and investing in inter-regional transfer and storage infrastructure. This evidence base can inform policy, infrastructure planning and strategic investment in decarbonising off-road vehicles in Great Britain.
Keywords: Non-road Mobile Machinery (NRMM); Off-Road Mobile Machinery (ORMM); NRMM Decarbonisation Pathways; Balanced Net Zero Pathway; Hydrogen Allocation Rounds (HAR); Hydrogen Supply-Demand NUTS 1 Mapping